Fall Fashion Note: Finer Dry Cleaning for America - Dow Chemical Company (1945)
Color print advertisement for Dowclene synthetic solvents manufactured and sold by the Dow Chemical Company for use in dry-cleaning, among other applications. The advertisement shows a smartly dressed woman in a skirt suit, hat and gloves. The accompanying text describes the use of Dowclene and other Dow solvents in dry cleaning, noting that "these superior dry cleaning solvents have fulfilled their war duties." This advertisement appeared in a 1945 edition of The Saturday Evening Post.
Keywords: Advertising; Dow Chemical Company; Chemical industry; Corporations; Solvents; Dry cleaning; World War (1939-1945); Women in advertising; Advertising, Industrial; Solvents industry